2016
DOI: 10.1016/j.jpeds.2016.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Reliability of the Respiratory Physical Examination in Premature Infants: A Multicenter Study

Abstract: Objective To measure the inter-rater reliability of 7 visual and 3 auscultatory respiratory physical examination findings at 36–40 weeks’ postmenstrual age in infants born less than 29 weeks’ gestation. Physicians also estimated the probability that each infant would remain hospitalized for 3 months after the examination or be readmitted for a respiratory illness during that time. Study design Prospective, multicenter, inter-rater reliability study using standardized audio-video recordings of respiratory phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…In this study, we were unable to verify accuracy of the scores assigned and this can be an area of difficulty even among experienced providers. A recent study showed very poor inter-rater reliability (IRR) in aspects of the respiratory exam of term-corrected infants between attending neonatologists and pulmonologists [ 18 ]. As the author points out, these clinicians, however experienced, had no standardized training for the assessment they were performing.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we were unable to verify accuracy of the scores assigned and this can be an area of difficulty even among experienced providers. A recent study showed very poor inter-rater reliability (IRR) in aspects of the respiratory exam of term-corrected infants between attending neonatologists and pulmonologists [ 18 ]. As the author points out, these clinicians, however experienced, had no standardized training for the assessment they were performing.…”
Section: Discussionmentioning
confidence: 99%
“…It is encouraging to observe that this simple, noninvasive bedside technology was able to demonstrate differences in the acoustic qualities of breath sounds between preterm and term babies, given they were all self‐ventilating in air, and such differences may not be detected by traditional auscultation. It is well‐known that traditional auscultation is impaired by interobserver subjectivity and physician experience, particularly in the preterm cohort, which is one of the reasons groups such as ours are investigating the use of the DS in pediatric medicine. We chose to study well infants first in this proof of concept paper using the DS and computerized analysis, allowing us to obtain a set of normal values without interference from ventilatory devices and significant lung pathology, before embarking on further study of infants requiring respiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…When assessing for wheezing, Bekhof et al 19 reported only fair inter-observer variation ( ϭ 0.36) in 27 dyspneic children filmed in the emergency room. Jensen et al 18 reported inconsistent inter-ob- 27 reported poor to fair agreement ( Ͻ 0.4) for wheezing, crackles, and rhonchi using 20 videos from 10 adults and 10 children. When we analyzed the results by grouped lung sound recordings, concordance tended to move to the middle of the isolated lung sound recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Mr Adasme is affiliated with Universidad Andres Bello, Escuela de Kinesiologia, Facultad de Ciencias de la Rehabilitación, Santiago, Chile; Departamento de Salud Pública y Epidemiología, Universidad de los Andes, Santiago, Chile. Mr Arellano is affiliated with Escuela de Kinesiologia Some studies [16][17][18] found fair to moderate inter-observer agreement between health professionals (eg physicians, nurses, physiotherapists) for the recognition of lung sounds. However, these studies were designed to test clinical scores that were limited to wheezes as the only lung sound.…”
Section: Introductionmentioning
confidence: 99%